Correction to: Frequency and predictors of health services use by native Hawaiians and Pacific islanders: evidence from the U.S. National Health Interview Survey - Marie-Rachelle Narcisse; Holly Felix; Christopher R. Long; Teresa Hudson; Nalin Payakachat; Zoran Bursac; Pearl A. McElfish (BMC, 2018)
Following publication of the original article [1], the author reported the following errors in Table 1 and Table 2.